Stress Management Among Students: Conventional and Islamic Perspectives - Ahmad Sudan, Salmi (2019)
Scholars, counsellors and medical practitioners have agreed on the notion that stress emanates from any type of adversity, sickness and other life trials. In other words, stress is a reality of life that humans have to deal with; it could be mild and it could be severe; it could be detected or otherwise. There are natural, spiritual and medical ways to reduce it; or deal with it. And these mechanisms differ from one individual to the other. Natural ways to treat or minimize constitute; meditation, exercise, massage, organize one’s life, eating healthy ways, limiting the time spent on the internet and mobile-phone usage as well as avoiding caffeine, alcohol, and nicotine. Being religious or spiritual helps reducing the pain of adversities; strengthens the inner entities, enhances positivity and increases the purity of soul, body and mind. All religions regardless of their identity, history and geographical location preach calm mind, healthy consciousness, and positive thought; these properties assist patients of stress regardless of their religious belief system. The believe that there is an ultimate power (Allah, God) also contributes to the wellbeing and the defence mechanism of the patient. In fact, religious individuals benefit from their faith and prayers in diverse ways and levels as they maintain strong sense of tranquillity, peace, and confidence; as well as strong inner capabilities to cope with stress. It was early 1950s when scholars have started to focus on stress related studies. Stress is a mental or physical phenomenon; it is also a state of physical or mental tension that causes emotional distress; a complex phenomenon which actually depends on the dispositions, environmental conditions, experiences and situations within which the individual lives. Stress nonetheless, stems from stressor. The later could be anything that challenges an individual’s adaptability on the environment he or she lives in or it could be a psychological or biological factor as well as social factors. Students are one of the first and weakest victims of stress as they face immense stressors during their studies; they must deal with financial, relationship and academic difficulties.